SIKAP DAN MOTIVASI PETANI DALAM BUDIDAYA TANAMAN SEMANGKA DI LAHAN PASIR PANTAI, KABUPATEN PURWOREJO, JAWA TENGAH - Kusumaningrum, Arta; Rahmawati, Fitri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Attitude and motivation are two important components in cultivating watermelon plants in coastal sandy land, Purworejo Regency. There were 2 objectives of this study, namely 1) to determine the attitudes of farmers in the cultivation of watermelons in coastal sandy land, Purworejo Regency and 2) to determine the motivation of farmers in watermelon cultivation in coastal sandy land, Purworejo Regency. Respondents involved in this study were 60 farmers in Grabag District, Ngombol District, and Purwodadi District. The research was conducted by purposive sampling, which was carried out in accordance with the research objectives. The analysis used was Likert scale and class intervals. They were used to determine the level of attitude and motivation of farmers in watermelon cultivation in coastal sandy land, Purworejo Regency. The Likert scale used were the SS scale (Strongly Agree), S (Agree), R (Doubtful), TS (Disagree), STS (Strongly Disagree) while class intervals were divided into 3 categories, namely high, medium, and low categories. The results of this study were 1) the attitude of farmers in watermelon cultivation in the coastal sandy land of Purworejo Regency, Central Java was medium. This study showed that many farmers had a tendency to utilize coastal sandy land for watermelons cultivation in Purworejo Regency and 2) the motivation of farmers in cultivating watermelons in coastal sandy land in Purworejo Regency, Central Java was medium as well. Therefore, it revealed that many farmers had been motivated to utilize coastal sandy land to cultivate watermelon plants in Purworejo Regency.